The antimalarial drug primaquine targets Fe–S cluster proteins and yeast respiratory growth - Lalève, Anaïs; Vallieres, Cindy; Golinelli-Cohen, Marie-Pierre; Bouton, Cécile; Song, Zehua; Pawlik, Grzegorz; Tindall, Sarah M.; Avery, Simon V.; Clain, Jérôme; Meunier, Brigitte (Elsevier, 2016)
Malaria is a major health burden in tropical and subtropical countries. The antimalarial drug primaquine is extremely useful for killing the transmissible gametocyte forms of Plasmodium falciparum and the hepatic quiescent forms of P. vivax. Yet its mechanism of action is still poorly understood. In this study, we used the yeast Saccharomyces cerevisiae model to help uncover the mode of action of primaquine. We found that the growth inhibitory effect of primaquine was restricted to cells that relied on respiratory function to proliferate and that deletion of SOD2 encoding the mitochondrial superoxide dismutase severely increased its effect, which can be countered by the overexpression of AIM32 and MCR1 encoding mitochondrial enzymes involved in the response to oxidative stress. This indicated that ROS produced by respiratory activity had a key role in primaquine-induced growth defect. We observed that Δsod2 cells treated with primaquine displayed a severely decreased activity of aconitase that contains a Fe–S cluster notoriously sensitive to oxidative damage. We also showed that in vitro exposure to primaquine impaired the activity of purified aconitase and accelerated the turnover of the Fe–S cluster of the essential protein Rli1. It is suggested that ROS-labile Fe–S groups are the primary targets of primaquine. Aconitase activity is known to be essential at certain life-cycle stages of the malaria parasite. Thus primaquine-induced damage of its labile Fe–S cluster – and of other ROS-sensitive enzymes – could inhibit parasite development.